A case of vasculogenic mesenchymal tumor in the mediastinum: whole-exome sequencing reveals origin from pre-existing germ cell tumor - Fujii, Hirotake; Yamada, Yosuke; Yamamura, Kentaro; Ishida, Yoshihiro; Tsujimura, Marina; Matsumoto, Kazuhisa; Tanaka, Satona; Date, Hiroshi; Nishikawa, Tadaaki; Yoshida, Yukihiro; Kashima, Jumpei; Yatabe, Yasushi; et al. (Virchows Archiv, 2023)
Vasculogenic mesenchymal tumor (VMT), a primitive mesenchymal neoplasm enriched by various-sized atypical vessels, is a new entity that develops in mediastinal germ cell tumors (GCTs) with yolk sac tumor (YST) components after chemotherapy. Notably, patients with VMT in the residual GCT have increased risk of developing sarcomas or hematopoietic malignancies. Here, we report a late-teenage male patient with residual teratoma and high-grade VMT after chemotherapy for a mediastinal mixed GCT, including YST. Whole-exome sequencing revealed biallelic inactivation of TP53 and extensive copy number alterations that suggested whole-genome doubling. The biopsy tissue of the mixed GCT before chemotherapy exhibited overlapping genetic alterations to those in the VMT. Immunohistochemical analyses of the VMT showed that the abnormal vessels were positive for cytokeratin, glypican 3, EZH2, and IMP3. The findings that VMT inherits the genetic alterations of pre-existing mixed GCT and exhibits a partly YST-like immunophenotype might contribute to its clinical aggressiveness.